Enhancing Farmer Engagement in Climate Policy: Recap - Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This PowerPoint Presentation highlights the critical role of farmers in climate change negotiations, the role agriculture and food systems in climate change, scaling of mitigation and adaptation actions and finance adaptation and resilience building in the sector, the PACJA's experiences related to advocacy and messaging and the evaluation of agriculture in the climate negotiations. The presentation notes the importance of engagement opportunities for farmers, working to the policy cycle, different policy vehicles, stakeholder mapping and building partnerships for both technical and financial support. The objective and four outcomes of the PACJA-EAFF partnership are elaborated focused on strengthening voices shaping national climate adaptation processes, increasing accountability of key stakeholders delivering financial commitments, coordination of CSO advocacy in decision making and production of research from Africa.